THE VALUE OF PREOPERATIVE MEDICAL TESTING FOR VITREORETINAL SURGERY. Issue 2 (February 2015) - Shalwala, Ajay; Hwang, Richard Y.; Tabing, Ariana; Sternberg, Paul; Kim, Stephen J.
Abstract : Purpose: To determine whether preoperative medical testing reduces the risk of postoperative systemic adverse events after vitreoretinal surgery. Methods: Retrospective cohort study at a single academic university hospital involving a total of 2, 215 patients undergoing vitreoretinal surgery. Medical charts of 2, 215 patients who underwent vitreoretinal surgery between January 2002 and November 2011 at Vanderbilt University were reviewed for baseline comorbidities, preoperative testing, type of anesthesia during surgery, and systemic adverse events occurring within 30 days after surgery. Main outcome measures were the association of baseline characteristics and preoperative testing with postoperative systemic adverse events. Results: Approximately a half of patients had electrolyte, renal function, and electrocardiogram evaluation. The most common comorbidities were hypertension (53%), diabetes mellitus (37%), and coronary artery disease (18%). The most common preoperative testing performed was blood glucose (58%). A total of 102 systemic adverse events occurred in 89 of 2, 215 patients (4%) within the first 30 days after surgery with the majority (72%) occurring within the first 24 hours. The most common adverse event was bradycardia (34%) followed by desaturation (25%). Patients with a history of coronary artery disease, asthma, chronic renal disease, or receiving general anesthesia had a 2.04 ( P = 0.01), 2.18 ( P = 0.03), 2.76 ( P < 0.01), and 3.72 ( P < 0.001) increased odds of developing postoperative systemic adverse events, respectively. Multivariate logistic regression analysis demonstrated no significant correlation between preoperative testing and postoperative adverse events. Conclusion: Incidence of postoperative systemic adverse events after vitreoretinal surgery was 4% and was significantly increased in patients with coronary artery disease, asthma, chronic renal disease, or receiving general anesthesia. In this series, preoperative testing did not measurably influence rates of postoperative systemic complications. Abstract : In this series, the incidence of postoperative systemic complications after vitreoretinal surgery was 4% and significantly increased in patients with coronary artery disease, asthma, chronic renal disease, or receiving general anesthesia. Preoperative testing did not measurably influence rates of postoperative adverse systemic events.